Constraints on oxen cultivation in the Sahel - Delgado, Christopher L.; McIntire, John (Wiley, 1982)
Ox‐powered cultivation is common in parts of the Sahel, yet most farmers in the region continue to cultivate manually. Insights from oxen farms in Mali are compared to nonadopters in Upper Volta. Ox‐driven technology in the Sahel may be more labor shifting than labor saving. Linear programming models indicate a prohibitive opportunity cost of extra labor required for team maintenance and use on small, rainfed farms growing traditional millets and sorghums in Upper Volta. Farm simulations suggest that ox plowing increases cash crop acreage, but clearly profitable adoption requires companion innovations to boost labor productivity in peak periods.